Analisis Faktor Yang Mempengaruhi Penerimaan Pengguna Aplikasi Elektronik Renumerasi Kinerja (E-RK) Menggunakan Metode UTAUT dan SDT (Studi Kasus : Pemerintah Kabupaten Musi Rawas) - Rifan Fadilah; Edi Surya Negara (Jurnal Ilmiah Matrik, 2022)
The E-RK application is an application that has an impact on government employee performance assessment through an electronic system. The purpose of this study is to determine the level of acceptance and users of the use of the E-RK application within the Musi Rawas Regency Government by using the Unified Theory of Acceptance and Use Technology and Self Determination Theory approach. . The type of data used is primary data obtained from questionnaires. The number of samples was 100 employees, then the data obtained were analyzed using the Structured Equation Model-Partial Least Square (SEM-PLS) method using smartPLS software. The results showed 3 out of 10 hypotheses that had a significant positive effect, namely the variable perception of the relationship to behavioral intention with a path coefficient value of 0.273 and a t-statistic value of 3.199, an anatomical perception variable on behavioral intention with a path coefficient value of 0.200 and a t-statistic value of 2.161, and the variable behavioral intention to use behavior with a path coefficient value of 0.544 and a t-statistic value of 5.231